PENGELOLAAN DIKLATPIM TINGKAT IV PADA BADAN PENDIDIKAN DAN PELATIHAN KOTA LUBUKLINGGAU - Lusiana Lusiana; Manap Somantri; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
The objective of this study is to describe the management of forth level leadership training at Education and Training Center of Lubuklinggau City. The method used in this study is descriptive qualitatif. The technique of collecting the data through interview, observations and documentation. The result of the research show that the the management of forth level leadership training at Education and Training Center of Lubuklinggau City implemented with the goal of building the civil servants’ operational leadership competencies who will or who have occupied echelon IV. The capability is the ability to plan the agency's activities and lead the implementation of these activities. that the the management of forth level leadership training at Education and Training Center of Lubuklinggau City has managed by structural trainning sector and the division head of leadership training as a tecnical implementation of the activities.